Using social media in the wine business. Issue 2 (2014) - Gergely Szolnoki; Dimitri Taits; Moritz Nagel; Alessio Fortunato
<x xml:space="preserve"> Abstract </x> Purpose – This paper aims to conduct two studies to investigate the use of social media tools by wineries in Germany and assess the impact of Facebook membership on customers by comparing them with customers who were not members. Today, a vast number of books and studies are being published about social media in general, but less is known about their usage and effectiveness in the wine industry. Design/methodology/approach – The first study was conducted among 321 German wineries. It focused on the attitudes and preferences of the winemakers regarding social media, and it analysed the daily use of this new communication tool. The second study took place in August 2012, and it set out to define the value that accrued to a winery from having Facebook fans. This analysis was based on an online survey with customers of the winery as well as on a comparative analysis of the buying patterns of customers who were Facebook fans and those who were not. The analysis compared the turnover from the purchases of both groups over a period of three years. Findings – It was determined that 60 per cent of German wineries did communicate with their customers using social media. Facebook was the most important social media channel, followed by Twitter and YouTube. Of the winemakers interviewed, 40 per cent planned, in the near future, to implement additional activities involving social media. The consumer study proved that Facebook fans had a higher turnover compared to the non‐Facebook fans of the winery studied. This finding emphasises the loyalty of Facebook fans. In addition, the study revealed that Facebook fans are open to receiving sales offers from the company which they support. Practical implications – Winery owners should be aware of the effectiveness of this modern communication tool. This is not only because Facebook fans generate a much higher turnover but also because of the possibility that they are interested in additional special offers on Facebook, which could mean an expansion of the available sales channels. Originality/value – To our knowledge, this kind of overview about the Germany wine sector as well as about the value of a Facebook‐fan of a winery has not yet been undertaken.